High-precision measurement of the atomic mass of the electron: letter - Sturm, Sven; Köhler, Florian; Zatorski, Jacek; Wagner, A.; Harman, Zoltán; Werth, G.; Quint, W.; Keitel, Christoph H.; Blaum, Klaus (Nature, 2014)
A very precise measurement of the magnetic moment of a single electron bound to a carbon nucleus, combined with a state-of-the-art calculation in the framework of bound-state quantum electrodynamics, gives a new value of the atomic mass of the electron that is more precise than the currently accepted one by a factor of 13.